Salicylic acid-loaded gelatin methacryloyl (GELMA) microneedles as a potential drug delivery system in plant diseases - ULAĞ, SONGÜL (My University, 2024)
In this research, gelatin methacryloyl (GELMA) was used as a matrix material to obtain microneedles (MNs), and salicylic acid (SA) was added to this solution to investigate the release behavior of the SA from the needles. The scanning electron microscope (SEM) images showed that the uniform conical shape of MN structures was observed. According to the compression test results, MNs could penetrate deeply into plant tissue without breaking due to their practical toughness. The release behavior of the SA was carried out in vitro conditions and completed in 24 h.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)